استخلاص الزيوت الاساسية من نبات الرشاد البري(Lepidium aucheri boiss) و دراسة فعاليتها الحيوية - حسام محمد كريدي; مريم ماجد كاظم (مجلة علوم ذي قار, 2019)
The present study amide to extracts the essential oils from Lepidium aucheri  boiss ,where  it  was   collected  in   March  2015 from   the   northern  of   Nasiriyah  city  and  it   was  classified . it  was extracted  from  plants  by  Clevenger's  Apparatus  to  be  finally  getting around 26.45g of essential oil of 24Kg plant .Then study the bioactivity of this essential oils ,the extracted essential oils from the plant didn’t showed any toxicity toward the red blood cells. The antibacterial properties was used  five types of bacteria, Cram positive strain (Staphylococcus aureus, Streptococcus pyogenes and Enterobacter sp.) and Cram negative strain (Escherichia coli, Pseudomonas aeruginosa),These moleules showed antimicrobial activites against gram negative and gram positive bacterial . The activity of the concentration 100% showed the highest percentage inhibition there are (20mm) towards bacteria Staphylococcus and E.coli bacteria showed less inhibition ratio there are (7mm) at the same concentration .In the test of antifungal properties used four types of fungus which Asperggillus niger and Asperggillus terrus and Asperggillus flavus and Candida albicans .The results showed the highest inhibition of the fungus at concentration 100% towards A.niger where the scale inhibition is 12 mm, while the other fungi have shown high resistance toward all the prepared concentration ,especially C.albicans.